Walking the sweet orange chain: agri-food geographies of citrus losses - Ugoh, Sarem (2018)
Food waste in recent years has become an international priority because of the large amounts of food wasted from farm to fork. In low-income countries like Nigeria, losses are significantly higher along the food chain from production to retail. There is a dearth of research that considers various crop value chains in different geographical regions and the prevailing conditions that influence these losses. Nigeria produces 3.9 million metric tonnes of citrus annually and it estimated that 30-70% is lost to postharvest losses.